Stellar laboratories: IX. New Se v, Sr iv-vii, Te vi, and I vi oscillator strengths and the Se, Sr, Te, and I abundances in the hot white dwarfs G191−B2B and RE 0503−289 - Rauch, Thomas; Demleitner, Markus (Astronomy and astrophysics, 2017)
Context. To analyze spectra of hot stars, advanced non-local thermodynamic equilibrium (NLTE) model-atmosphere techniques are mandatory. Reliable atomic data is crucial for the calculation of such model atmospheres. Aims. We aim to calculate new Sr iv-vii oscillator strengths to identify for the first time Sr spectral lines in hot white dwarf (WD) stars and to determine the photospheric Sr abundances. To measure the abundances of Se, Te, and I in hot WDs, we aim to compute new Se v, Te vi, and I vi oscillator strengths. Methods. To consider radiative and collisional bound-bound transitions of Se v, Sr iv - vii, Te vi, and I vi in our NLTE atmosphere models, we calculated oscillator strengths for these ions. Results. We newly identified four Se v, 23 Sr v, 1 Te vi, and three I vi lines in the ultraviolet (UV) spectrum of RE 0503−289. We measured a photospheric Sr abundance of 6.5+ 3.8-2.4× 10-4 (mass fraction, 9500-23 800 times solar). We determined the abundances of Se (1.6+ 0.9-0.6× 10-3, 8000-20 000), Te (2.5+ 1.5-0.9× 10-4, 11 000-28 000), and I (1.4+ 0.8-0.5× 10-5, 2700-6700). No Se, Sr, Te, and I line was found in the UV spectra of G191−B2B and we could determine only upper abundance limits of approximately 100 times solar. Conclusions. All identified Se v, Sr v, Te vi, and I vi lines in the UV spectrum of RE 0503−289 were simultaneously well reproduced with our newly calculated oscillator strengths.